The sandman book of dreams - Gaiman, Neil; Kramer, Ed (New York, New York HarperTorch, 1996)
Fantasy stories. In Will Shetterly's Splatter, killers decide to show a novelist how it's really done, Karen Haber's A Bone Dry Place is set in a suicide-prevention clinic, and in John Ford's Chain Home, Low a sleeping virus strikes a group of wartime pilots.
Frontispiece : death / Clive Barker -- Preface / Frank McConnell -- Masquerade and high water / Colin Greenland -- Chain home, low / John M. Ford -- Stronger than desire / Lisa Goldstein -- Each damp thing / Barbara Hambly -- The birth day / B.W. Clough -- Splatter / Will Shetterly -- Seven nights in Slumberland / George Alec Effinger -- Escape artist / Caitlín R. Kiernan -- An extra smidgen of eternity / Robert Rodi -- The writer's child / Tad Williams -- Endless sestina / Lawrence Schimel -- The gate of gold / Mark Kreighbaum -- A bone dry place / Karen Haber -- The witch's heart / Delia Sherman -- The mender of broken dreams / Nancy A. Collins -- Ain't you 'most done? / Gene Wolfe -- Volóság and Élet / Steven Brust -- Stopp't-clock yard / Susanna Clarke -- Afterword : death / Tori Amos -- Biographical notes.
Short stories based on the comic book series The Sandman.